Insight Into the Molecular Dynamic Simulation Studies of Reactive Oxygen Species in Native Skin Membrane - Yadav, Dharmendra K.; Kumar, Surendra; Choi, Eun-Ha; Sharma, Praveen; Misra, Sanjeev; Kim, Mi-Hyun (Frontiers in Pharmacology, 2018)
In recent years, the role of reactive oxygen species (ROS) in regulating cancer cell apoptosis, inflammation, cell ischemia, and cell signaling pathways has been well established. The most common sources of intracellular ROS are the mitochondrial electron transport system, NADH oxidase, and cytochrome P450. In this study, we investigated the dynamics and permeability of ROS using molecular dynamics (MD) simulations on native skin-lipid bilayer membranes. Native skin-lipid bilayers are composed of ceramide, cholesterol, and free fatty acid in an almost equal molar ratio (1:1:1). Dynamic distribution studies on ROS, i.e., hydrogen peroxide (H2O2) and O2 (1O2 by analogy), revealed that these species interact with cholesterol as a primary target in lipid peroxidation of the skin-lipid bilayer. Moreover, the permeability of ROS, i.e., H2O2, hydroxyl radicals (HO), hydroperoxy radical (HOO), and O2, along the skin-lipid bilayer was measured using free energy profiles (FEPs). The FEPs showed that in spite of high-energy barriers, ROS traveled through the membrane easily. Breaching the free energy barriers, these ROS permeated into the membrane, inflicting oxidative stress, and causing apoptosis. Collectively, the insight acquired from simulations may result in a better understanding of oxidative stress at the atomic level.